Behaviour in Intrahepatic Cholestasis of Pregnancy - Notev, Dimitar (International Journal of Innovative Research in Medical Science, 2022)
Intrahepatic (obstetric) cholestasis of pregnacy (ICP) is a unique hepatobiliary condition that manifests itself with itching, jaundice, an increase in the serum concentration of bile acids and poses a risk of complications for both the mother and the baby. ICP is a reversible type of hormonally influenced cholestasis. It develops during the third trimester, when hormone concentrations are at their peak. After the birth of the baby, when the production of the placental hormone stops, the bile flow returns to normal and the symptoms disappear.